1988
DOI: 10.1530/jrf.0.0830901
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced secretion of oxytocin from bovine granulosa cells treated with adrenal steroids

Abstract: Bovine granulosa cells were exposed in vitro to various adrenal steroids (cortisol, cortisone, corticosterone, aldosterone; 1 mumol/l), in the presence and absence of stimulation by ascorbic acid (0.5 mmol/l), to determine the possible effects of these hormones on ovarian oxytocin and progesterone secretion. Only cortisol produced a consistent stimulation of the cells; the response was dose-related over the range 0.01 to 1.0 mumol/l and was greatly enhanced in the presence of ascorbate. The secretion of oxytoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Because glucocorticoid is only synthesized in the adrenal cortex and is delivered systemically to the whole body, the presence of 11 -HSD is crucial for glucocorticoid target organs such as the liver and lung for modulating local concentrations of active glucocorticoid (Krozowski et al 1999). The expression of 11HSD1 and 11HSD2 in bovine ovarian tissues, together with the reported direct glucocorticoid action in cultured follicular cells (Luck 1988, Kawate et al 1993, Spicer & Chamberlain 1998, indicates that the bovine ovary is a glucocorticoid target organ which is also capable of modulating the local glucocorticoid environment.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Because glucocorticoid is only synthesized in the adrenal cortex and is delivered systemically to the whole body, the presence of 11 -HSD is crucial for glucocorticoid target organs such as the liver and lung for modulating local concentrations of active glucocorticoid (Krozowski et al 1999). The expression of 11HSD1 and 11HSD2 in bovine ovarian tissues, together with the reported direct glucocorticoid action in cultured follicular cells (Luck 1988, Kawate et al 1993, Spicer & Chamberlain 1998, indicates that the bovine ovary is a glucocorticoid target organ which is also capable of modulating the local glucocorticoid environment.…”
Section: Discussionmentioning
confidence: 98%
“…The ovary expresses glucocorticoid receptor (GR) and direct action of glucocorticoid on various ovarian functions has been reported in several species (Hsueh & Erickson 1978, Luck 1988, Fitzpatrick & Richards 1991, Kawate et al 1993, Urban et al 1994, Spicer & Chamberlain 1998, Gaytan et al 2002, Yang et al 2002. The ovary does not produce glucocorticoid per se and the access of active glucocorticoid (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been well documented that ovulation is an inflammatory-like reaction that involves many inflammatory mediators such as leucocytes, cytokines, prostaglandins, steroids and proteases (Espey 1980, 1994, Richards et al 2002. Glucocorticoid has been shown to regulate these factors in the ovary of rats and cattle (Adashi et al 1981, Schoonmaker & Erickson 1983, Luck 1988, Wang & Leung 1989, Jia et al 1990, Kol et al 1998, Irahara et al 1999. Glucocorticoid has also been suggested to protect ovulating follicles by suppressing apoptosis in granulosa cells and inducing apoptosis in infiltrating leucocytes (Amsterdam & Sasson 2002, Sasson & Amsterdam 2003.…”
Section: Glucocorticoid Metabolism In Bovine Cocmentioning
confidence: 99%
“…As an autocrine factor, OT supports the growth and maturation of the ovarian follicles (Voss andFortune 1993, Jo andFortune 2003). In addition, Besides the prostaglandins and oestrogens in luteal cells and LH, and FSH in granulosa cells (Wathes 1989, Kotwica et al 1990, cortisol was also found to increase OT secretion from bovine ovarian cells (Luck 1988. Glucocorticosteroids (GCs) are steroid hormones produced in the zona fasciculata and the reticulate of the adrenal cortex.…”
Section: Introductionmentioning
confidence: 99%